AVALIAÇÃO TOXICOLÓGICA E AÇÃO ANTI-INFLAMATÓRIA E ANTINOCICEPTIVA DAS NANOCÁPSULAS CONTENDO MELOXICAM EM UM MODELO DE NEUROPATIA DIABÉTICA EM CAMUNDONGOS - Villalba, Benonio Terra (2015)
Neuropathic pain is a challenge in the therapeutic approach. Although there is a wide range of analgesics, they often are not effective. Furthermore, the use of long-term drug can caused significant adverse effects. Therefore, the mains of this study was to investigate a new pharmacological alternative for the treatment of neuropathic pain using meloxicam-loaded nanocapsules (M-NC) in mice, as well as to study the toxicological effects of nanoparticles in the liver and stomach of animals. Male Swiss mice were used. In toxicological study, mice were divided into three groups: control - treated with blank nanocapsules (B-NC); nano - treated with M-NC; and free - treated with free meloxicam (M-F). Treatments were performed daily for five consecutive days at dose of 10 mg/kg, intragastrically (i.g.). On the seventh day, animals were killed and liver, stomach and blood were removed for analysis. M-NC treatment did not cause stomach ulcerogenic parameters and lipid peroxidation in the stomach and liver, while M-F caused ulcerogenic changes in the stomach and increased lipid peroxidation in the stomach and liver. M-NC and M-F treatment promoted mild histological alterations in the liver and stomach of animals. Biochemical parameters in the blood were not changed in any of groups tested. In the diabetic neuropathy, animals were initially divided into two groups: I - no diabetic (treated with 0,9 % saline, 10 ml/kg); II - diabetic (streptozotocin (STZ), 100mg/kg). These treatments were performed during three consecutive days. One week after the first injection of STZ, animals were subjected to six hours fasting for determination of blood glucose levels. After glucose measurement, animals were treated with M-NC or B-NC or M-F and behavioral tests (time 0) (mechanical and thermal hypersensitivities) were performed. M-NC and M-F were administered at dose of 5 mg/kg by i.g. via. Twenty-four hours after treatments, animals were again submitted to behavioral tests (mechanical and thermal hypersensitivities), open field test and printing paws. After, animals were killed; blood was collected for glucose measurement in the blood, glycosylated hemoglobin and determination of cytokines; as well as sciatic nerve was collected for optical and electronics microscopies and immunohistochemistry. M-NC treatment restored nociception, blood glucose levels, gait, and changes in sciatic nerve immunohistochemical and ultrastructural, while partially restored cytokine levels in the blood and not restored locomotor and exploratory activities of animals. M-F treatment did not restore behavioral, 14 immunohistochemical and ultrastructural changes, but partially restored the cytokines levels in the blood. In conclusion, M-NC showed a more antinociceptive and anti-inflammatory effects than M-F in the treatment of diabetic neuropathy. Moreover, M-NC showed low toxicity in the stomach and liver of mice.